2018
DOI: 10.1007/s40258-018-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ACA on Preventive Care Disparities

Abstract: Early effects of the ACA's provision of free preventive care are significant for Hispanics and African Americans. Further research is needed for the later years as more individuals became aware of these benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Our results show that black women had the lowest decline in mammography and women from other minorities had the lowest decline in Pap test use compared to white women (Table 3 and Table 4). A recent study found the ACA provision to be associated with improved mammography and pap tests among Hispanics and African Americans [31]. Looking at overall utilization, black women had the highest rate of mammogram and pap tests use (mammogram: 81.48%, pap tests: 74.73%) (Table 3 and Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that black women had the lowest decline in mammography and women from other minorities had the lowest decline in Pap test use compared to white women (Table 3 and Table 4). A recent study found the ACA provision to be associated with improved mammography and pap tests among Hispanics and African Americans [31]. Looking at overall utilization, black women had the highest rate of mammogram and pap tests use (mammogram: 81.48%, pap tests: 74.73%) (Table 3 and Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…42 While some studies suggest that higher screening rates reported by non-Hispanic Black individuals may be an artifact associated with overreporting, 43 , 44 other studies suggest that the Patient Protection and Affordable Care Act has been instrumental in countering low screening rates that were reported historically among minority racial and ethnic groups. 45 Should this be the case, we would anticipate changes in disparities in mortality in coming years. Our findings support prior reports of colorectal cancer screening being adversely associated with income and insurance status and skewed toward an older population.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that utilization of preventive services has increased since the implementation of the ACA’s preventive services provisions, but the improvements were minimal across all the essential health benefits (Hong et al, 2017). Another study showed that improvements in use of preventive services were more pronounced among Latinos and non-Latino “blacks” relative to non-Latino “whites” after the implementation of the ACA’s preventive services provisions (Agirdas and Holding, 2018), which suggests that racial and ethnic disparities in preventive services utilization have decreased. Improvements were not observed, however, among Asians as a single group (Agirdas and Holding, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that improvements in use of preventive services were more pronounced among Latinos and non-Latino “blacks” relative to non-Latino “whites” after the implementation of the ACA’s preventive services provisions (Agirdas and Holding, 2018), which suggests that racial and ethnic disparities in preventive services utilization have decreased. Improvements were not observed, however, among Asians as a single group (Agirdas and Holding, 2018).…”
Section: Introductionmentioning
confidence: 99%